Collision of two epidemics: prevalence of diabetes in tuberculosis patients in urban Ludhiana - Eruva, Vijayalakshmi; Samuel, Clarence James; Singh, Shavinder (International Journal Of Community Medicine And Public Health, 2020)
Background: Co-association between tuberculosis (TB) and diabetes has been observed for more than 2000 years. The burden of the both diabetes and tuberculosis is very high in India. Diabetes in TB patient decreases the success of anti-tubercular therapy and overall cure rates, which causes social and economic burden to country. The objective of the study was to find out the prevalence of diabetes mellitus in patients with tuberculosis under RNTCP treatment. Methods: This cross-sectional study was conducted in DOTS centers under Civil Hospital TU of Ludhiana, Punjab. 300 TB cases, above 18 years of age were included and screened for diabetes. Patients were interviewed regarding demographic profile and family history of diabetes. Height, weight, blood pressure, BMI and waist hip ratio were recorded. Results: The prevalence of diabetes in tuberculosis patients was found to be 21.3% (known diabetics- 6.3%, new diabetes cases- 15%). There was a statistically significant association of diabetes with older age and high BMI. Conclusions: Specific guidelines for management of the dual disease may help in improving the overall success of treatment.